Strengthening Coastal Construction Safety Through Community-Based OHS Socialization, Education, and Training in West Aceh - Zakia, Zakia; Sariani, Meylis; Yuri Salena, Inseun; Rafshanjani, M.Arrie; Febrianty, Dian; Hasdanita, Fitry (LPPM Universitas Jambi, 2024)
The implementation of Occupational Health and Safety (OHS) in port embankment construction is crucial for improving the security and durability of coastal infrastructure. The main goal of OHS is to prevent, reduce, or eliminate workplace accidents, which is particularly important given the potentially serious consequences of such incidents. This research focuses on the distribution and training of OHS practices, particularly stressing the proper use of personal protective equipment (PPE) to reduce accident risks. The program involved forming two groups of five people each, who participated in a structured socialization and training session. To assess the effectiveness of the program, participants were given pre- and post-activity questionnaires to measure their knowledge of OHS and safety building principles related to port embankment construction. The findings show that applying OHS principles led to significant improvements in safety measures and a reduction in workplace accidents. However, challenges persist, especially regarding the local community’s comprehension of OHS protocols and consistent PPE usage. Ongoing training and more stringent supervision are recommended to improve OHS implementation further. These enhancements would ensure the safety and well-being of workers on construction sites more effectively.